x+2y−z=3

−2x−y+z=−1

6x−3y−z=−7

Add first two equations:

-x+y=2 so y=x+2.

Substitute for y:

x+2(x+2)-z=3, 3x+4-z=3, 3x-z=-1; -2x-(x+2)+z=-1, -3x-2+z=-1, -3x+z=1, or 3x-z=-1; 6x-3(x+2)-z=-7, 3x-6-z=-7, 3x-z=-1, or z=3x+1.

So there is no unique solution, that is, there are many solutions.

We can find y and z given x. For example, x=0 gives us y=2 and z=1.

Other examples: x=1 gives y=3 and z=4; x=-1 gives y=1 and z=-2.

There are an infinite number of solutions. Any x will give solutions for y and z: y=x+2, z=3x+1, which can be written (x,x+2,3x+1).

- All categories
- Pre-Algebra Answers 12.3k
- Algebra 1 Answers 25.3k
- Algebra 2 Answers 10.5k
- Geometry Answers 5.2k
- Trigonometry Answers 2.6k
- Calculus Answers 6.1k
- Statistics Answers 3k
- Word Problem Answers 10.2k
- Other Math Topics 6.7k

81,954 questions

86,350 answers

2,238 comments

71,713 users